Network planning of the publishing process for the issue of the magazine - Demin, Dmitriy; Schwickerath, Horst; Schwickerath, Katharina (Technology audit and production reserves, 2020)
The object of research is the publishing process for the magazine’s release. One of the most problematic areas is the difficulty of competition between print publishers and media that provide information services on the web. Therefore, for publishers, it is especially important to ensure consistency of work within the entire publishing process based on its rational organization. In particular, the development of structural diagrams and relationships at different levels of preparation and implementation of publishing projects is relevant. Network planning methods are used in research. The obtained results suggest that the proposed structural scheme for managing the publishing process is successful. Due to the presence of the proposed links between the participants in the publishing process, the scheme provides the ability to plan each current issue of the magazine with a guarantee of the announced terms of the magazine’s release. The influence of two scenarios – pessimistic and optimistic – on the deadline is analyzed. It has been established that the pessimistic forecast does not allow for the specified target date if it is 1 time per quarter. The optimistic forecast provides the possibility of a guaranteed quarterly publication of the magazine – the target date for all publishing processes before the start of the finished circulation is 89–92 days. In the case of an optimistic forecast, the network schedule for publishing the magazine showed that all works within the publishing process, before the distribution of the current issue’s circulation, have a reserve of time. While in the implementation of the pessimistic scenario, only two works have a reserve of time – the design and approval of the design of the advertisement with the customer. The peculiarities of the proposed solutions are that the pessimism and optimism of the scenarios are determined in relation to those works for which everything depends only on the performer. In turn, these are exactly the works that do not require external approvals.